Abstract 4979: Cabozantinib eradicates advanced murine prostate cancer by activating neutrophil-mediated anti-tumor innate immunity - Patnaik, Akash; Swanson, Kenneth D.; Csizmadia, Eva; Gehring, Marina P.; Helenius, Katja; Pyzer, Athalia R.; Wang, Lily C.; Novak, Jesse; Elemento, Olivier; Thornley, Thomas B.; Asara, John M.; Clohessy, John G.; et al. (Cancer research (Chicago, Ill.), 2016)
Several kinase inhibitors targeting aberrant signaling pathways in tumor cells have been deployed in cancer therapy. However, their impact on the tumor immune microenvironment remains poorly understood. The tyrosine kinase inhibitor cabozantinib showed striking responses in cancer clinical trial patients across several malignancies. Here we show that cabozantinib rapidly eradicates invasive, poorly-differentiated PTEN/p53 deficient murine prostate cancer. This was associated with enhanced release of neutrophil chemotactic factors from tumor cells, including CXCL12 and HMGB1, resulting in robust infiltration of neutrophils into the tumor. Critically, cabozantinib-induced tumor clearance in mice was abolished by antibody-mediated granulocyte depletion or HMGB1 neutralization or blockade of neutrophil chemotaxis with the CXCR4 inhibitor, plerixafor. Collectively, these data demonstrate that cabozantinib triggers a neutrophil-mediated anti-tumor innate immune response, resulting in rapid tumor clearance. Citation Format: Akash Patnaik, Kenneth D. Swanson, Eva Csizmadia, Marina P. Gehring, Katja Helenius, Athalia R. Pyzer, Lily C. Wang, Jesse Novak, Olivier Elemento, Thomas B. Thornley, John M. Asara, John G. Clohessy, Kathy Kelly, Pier Paolo Pandolfi, Jacalyn M. Rosenblatt, David E. Avigan, Huihui Ye, Sabina Signoretti, Steven P. Balk, Lewis C. Cantley. Cabozantinib eradicates advanced murine prostate cancer by activating neutrophil-mediated anti-tumor innate immunity. [abstract]. In: Proceedings of the 107th Annual Meeting of the American Association for Cancer Research; 2016 Apr 16-20; New Orleans, LA. Philadelphia (PA): AACR; Cancer Res 2016;76(14 Suppl):Abstract nr 4979.